Modelagem hidrodinâmica e estudo morfológico do Lago Água Preta: um dos mananciais da Grande Belém - HOLANDA, Patrícia da Silva (Universidade Federal do Pará, 2014)
The natural conditions of water resources can be modified with the unsustainable use of them. For example, in Belém, capital of Pará State, Água Preta Lake has a history of degradation jeopardize the drinking water supply in Belém. Thus, the main contribution of this work is to develop a study on modeling hydrodynamic and morphological study of Água Preta Lake. Such study is carrid out through two data sources. The first is a bathymetric chart to date from 1975. This chart is avaliable in the archives of COSANPA. The second was performed with an ADCP and the dates from 2009. The modeling began with the development of models of terrain elevation to date from 1975 and 2009, also used for the morphological study of the lake. To assemble the hydrodynamic model were needed bathymetrics data, substrates data for the friction model of the underwater relief of the lake to calculate the coefficient of Manning; and boundary conditions. The hydrodynamic simulations, depths and velocities, are performed using the model of Saint-Venant shallow water. The simulated depths were compared to data available in the literature. The simulated depths and velocities and the morphological study were used to analysis water flow pattern and sedimentation trends in the lake.